2021
DOI: 10.3390/cancers13071653
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Pathway in Head and Neck Squamous Cell Carcinoma: Potential as a Diagnostic and Prognostic Marker

Abstract: Head and neck squamous cell carcinoma (HNSCC) is characterized by high rates of mortality and treatment-related morbidity, underscoring the urgent need for innovative and safe treatment strategies and diagnosis practices. Mitochondrial dysfunction is a hallmark of cancer and can lead to the accumulation of tricarboxylic acid cycle intermediates, such as succinate, which function as oncometabolites. In addition to its role in cancer development through epigenetic events, succinate is an extracellular signal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…They further reported that serum succinate level is increased in patients with non-small cell lung carcinoma and that serum succinate has the potential to be a biomarker of lung cancer [ 48 ]. A recent report reveals that serum succinate is a biomarker of human head and neck squamous carcinoma [ 107 ]. Taken together, these findings suggest that cancer cell secrete succinate into circulating blood to raise the blood level of succinate.…”
Section: Introductionmentioning
confidence: 99%
“…They further reported that serum succinate level is increased in patients with non-small cell lung carcinoma and that serum succinate has the potential to be a biomarker of lung cancer [ 48 ]. A recent report reveals that serum succinate is a biomarker of human head and neck squamous carcinoma [ 107 ]. Taken together, these findings suggest that cancer cell secrete succinate into circulating blood to raise the blood level of succinate.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease this inflammatory response, macrophages tend to use itaconate to inhibit SDH function and the proinflammatory responses 52 . In head and neck squamous cell carcinoma (HNSCC), the expression of SDHA is higher in the tumor tissues than in the tissue-matched normal mucosa, predicting a higher locoregional recurrence 53 . Our study showed that the increased ATF3 level could repress the TCA cycle-related gene SDHA 's expression, leading to a reduced mitochondrial respiration rate and ATP contents.…”
Section: Discussionmentioning
confidence: 99%
“…GPR91 expression also correlated with that of other receptors for inhibitory pathways, such as PD-L1, PD-L2, CD48, CD80, and CD86. GPR91 is not only highly expressed in ovarian cancer cells, so we may extrapolate that succinate exerts similar immune effects in other cancers, such as head and neck squamous cell carcinoma [ 79 ]. A recent study [ 76 ] also shows that succinate stimulates TAM marker gene expression, including Arg1 , Fizz1 , Mgl1 , and Mgl2, and is responsible for the upregulation of vascular cell adhesion molecule 1 (VCAM1) and CD11c on the surface of TAMs.…”
Section: Succinatementioning
confidence: 99%